Pengaruh Orientasi Pasar, Orientasi Kewirausahaan, dan Manajemen Pengetahuan melalui Keunggulan Bersaing terhadap Kinerja Pemasaran UMKM Pengolah Kopi di Kabupaten Tanah Datar - Fayi Afifah; Nofialdi Nofialdi; Widya Fitriana (Jurnal Sosio Agribisnis, 2022)
This study was aimed at describing the conditions and analyzing the influence of market orientation, entrepreneural orientation, and knowledge management through competitive superiority on the marketing performance of Coffee Processing MSMEs (Micro, Small, and Medium Enterprises) in Tanah Datar Regency. The type of data used was cross section data. Data were obtained from questionnaires and interviews to 87 respondents. Research variables include market orientation, entrepreneural orientation, knowledge management, competitive superiority, and marketing performance. Data were analyzed using the SEM (Structural Equation Model) analysis method using the SmartPLS 3.0 application. The results showed that MSMEs processing Coffee in Tanah Datar Regency had good market orientation, entrepreneural orientation, and knowledge management, high competitive superiority, but had a low marketing performance. Market orientation, entrepreneural orientation, and knowledge management affected the marketing perfomance. Competitive superiority did not affect the marketing performance. Market orientation and entrepreneural orientation did not affect the competitive superiority. Knowledge management showed a positive and significant relationship with the competitive superiority of the business. Competitive superiority did not show mediating impacts between market orientation, entrepreneural orientation, and knowledge management with marketing performance. Keywords: market Orientation; entrepreneural orientation; knowledge; competitive superiority; marketing performance